Premedication with simethicone and N-acetylcysteine in improving visibility during upper endoscopy: a double-blind randomized trial - Elvas, Luís; Areia, Miguel; Brito, Daniel; Alves, Susana; Saraiva, Sandra; Cadime, Ana T. (Endoscopy, 2017)
Background and study aim Upper endoscopy is the most common method for the diagnosis of upper gastrointestinal tract diseases. The aim of this study was to determine whether premedication with simethicone or N-acetylcysteine improves mucosal visualization during upper endoscopy.Patients and methods This was a randomized, double-blind, placebo-controlled study of 297 patients scheduled for upper endoscopy who were premedicated 15 – 30 minutes before the procedure with: 100 mL of water (placebo, group A); water plus 100 mg simethicone (group B); water plus 100 mg simethicone plus 600 mg N-acetylcysteine (group C). The primary outcome measure was the quality of mucosal visualization (score: excellent, adequate or inadequate). Results The addition of simethicone (group B) or simethicone plus N-acetylcysteine to the water (group C) improved the visualization scores of endoscopies compared with water alone (group A). In particular, groups B and C produced a significantly higher percentage of endoscopies with excellent visualization for the esophagus (91.1 % and 86.7 %, respectively, vs. 71.4 % in group A; P < 0.001) and stomach (76.2 % and 74.5 % vs. 38.8 % in group A; P < 0.001). For the duodenum, the use of simethicone also showed an increase in the endoscopies with excellent visualization compared with water alone (85.1 % vs. 73.5 %; P = 0.042). There were no significant differences in scores between groups B and C or between gastric scores in patients with previous subtotal gastrectomy (B and C vs. A): 60.0 % and 42.1 % vs. 28.6 % (P = 0.14). The rate of reported lesions was higher in group B but without statistical significance.Conclusions Premedication with simethicone resulted in better mucosal visibility. Such premedication might improve diagnostic yield, and should be considered for standard practice. Trial registered at ClinicalTrials.gov (NCT02357303).